Root-Lesion Nematodes Suppress Cabbage Aphid Population Development by Reducing Aphid Daily Reproduction - Hol, W. H. G.; Raaijmakers, Ciska E.; Mons, Ilse; Meyer, Katrin M.; van Dam, Nicole M. (Frontiers in Plant Science, 2016)
Empirical studies have shown that belowground feeding herbivores can affect the performance of aboveground herbivores in different ways. Often the critical life-history parameters underlying the observed performance effects remain unexplored. In order to better understand the cause for the observed effects on aboveground herbivores, these ecological mechanisms must be better understood. In this study we combined empirical experiments with a modeling approach to analyze the effect of two root feeding endoparasitic nematodes with different feeding strategies on the population growth of the aboveground feeding specialist aphid Brevicoryne brassicae on Brassica nigra. The aim was to test whether emerging differences in life history characteristics (days until reproduction, daily reproduction) would be sufficient to explain observed differences in aphid population development on plants with and without two species of nematodes. Aphid numbers were lower on plants with Pratylenchus penetrans in comparison to aphid numbers on plants with Meloidogyne spp. A dedicated experiment showed that aphid daily reproduction was lower on plants with P. penetrans (3.08 offspring female–1 day–1) in comparison to both uninfested plants and plants with Meloidogyne spp. (3.50 offspring female–1 day–1). The species-specific reduction of aphid reproduction appeared independent of changes in amino acids, soluble sugars or the glucosinolate sinigrin in the phloem. An individual-based model revealed that relatively small differences in reproduction rate per female were sufficient to yield a similar difference in aphid populations as was found in the empirical experiments.